Ethnochemistry Potential of Vines Contained in Lontar Usada Taru Pramana on Students’ Scientific Explanation Skills through Task-Based Learning - I. G. L. Wiratma; I. A. A. Yuliamiastuti (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This research focuses on the analysis of the ethnochemistry potential of the vines contained in the Lontar Usada Taru Pramana. Lontar Usada Taru Pramana is a note written on palm leaves about plants that are useful as medicines used as a reference for traditional Balinese medicine. This study aims to analyze the effectiveness of task-based learning that utilizes the ethnochemistry potential of vines contained in Lontar Usada Taru Pramana, on students’ scientific explanations skills. This research was conducted during the post-Covid-19 period in vocational and high schools with 234 students. This research was quantitative and applied The One-Group Pretest-Posttest Design with replication where there was no control class and all research subjects were given the same treatment. Task instructions were passed through pre-task, process task, and post-task. The type of task in learning is to make scientific studies of ethnochemistry by sharing personal experiences and solving problems. The data collection technique used tests as descriptive essay questions to measure students’ scientific explanation skills on some materials in booklets of Taru Pramana Lontar. The tests in this study described several components: plant classification, chemical content, benefits and methods of concocting it as medicine, and the scientific version of the Lontar Usada Taru Pramana composition. The effectiveness of task-based learning was analyzed using the N-Gain and T-test. The results of this study indicate that giving assignments based on Lontar Usada Taru Pramana in chemistry learning is effective in increasing students’ ability to explain the scientific study of vines as medicine. The N-gain results are in the high category of 0.76 for vocational students and 0.72 for high school students. While the T-test result shows that there is a significant difference between students’ pretest and posttest results in both vocational school and high school with a significance of .01. Students tend to correctly give scientific explanations to the plants they often encounter. This study shows that the ethnochemistry potential of the vines on Lontar Usada Taru Pramana can improve students’ scientific explanation skills. This study recommends elaborating chemistry concepts in the preservation of cultural heritage through transferring knowledge on using traditional and modern medicinal plants and their development in research.